Literature Review: Trends in the Development of Natural and Social Science Learner Worksheets in Primary Schools between 2019-2025 - Feronika, Shela Intan; Harianingsih, Harianingsih; Subali, Bambang; Ellianawati, Ellianawati (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study aims to analyze trends in the development of student worksheets in natural and social science learning at the primary school level during the 2019–2025 period. The method used is a literature review with a PRISMA approach applied to 25 selected articles out of 998 obtained through Publish or Perish. The PRISMA approach was implemented to transparently and systematically screen and select relevant articles through a flow diagram consisting of four stages: identification, screening, eligibility assessment, and inclusion. The results show that the most dominant learning model used in the development of natural and social science student worksheets is inquiry, followed by discovery learning, STEM, CTL, and the scientific approach. The developed worksheets have been proven effective in improving learning outcomes, conceptual understanding, critical thinking skills, and scientific literacy, as well as students’ motivation and learning independence. The implications of this study are significant for educators and material developers in designing innovative student worksheets that align with students’ needs, are consistent with the Merdeka Curriculum, and are relevant to the demands of 21st-century learning.